ANALISIS PENGARUH PROMOSI DIGITAL DAN KEPERCAYAAN TERHADAP PERILAKU KONSUMTIF MAHASISWA AKUNTANSI UNIVERSITAS MUHAMMADIYAH SURAKARTA DALAM BERBELANJA ONLINE DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI - Prihati, Ayu; Arifin, Atwal (LP2M Universitas Bina Bangsa, 2025)
This study aims to determine the influence of digital promotion and trust on the consumptive behavior of accounting students of the University of Muhammadiyah Surakarta in online shopping with religiosity as a moderation variable. The type of research used in this study is quantitative research. The type of data collection used in this study is primary data. This study uses the active student population in 2024 of the Accounting study program class of 2020 at the University of Muhammadiyah Surakarta. Sampling in this study uses the convenience sampling method, to find out the sample size of the population whose number will be known using the Slovin formula. In this study, the data collection instrument uses a questionnaire. The results of the study showed that the digital promotion variable did not have a significant influence on consumptive behavior, while digital trust had a significant effect on consumptive behavior, religiosity did not moderate the influence of digital promotion on consumptive behavior, religiosity moderated the influence of trust on the consumptive behavior of Accounting students of the University of Muhammadiyah Surakarta in online shopping